2020
DOI: 10.3389/fgene.2020.550515
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Analysis of Mammary Gland Tissues From Chinese Holstein Cows With Staphylococcus aureus Induced Mastitis

Abstract: Wang et al. Genome-Wide DNA Methylation Underlying S. aureus-Induced-Mastitis processes, especially the regulation of immune response to diseases. C m CGG DMEGs like IL6R, TNF, BTK, IL1R2, and TNFSF8 enriched in several immune-related GO terms and pathways indicated their important roles in host immune response and their potential as candidate genes for S. aureus mastitis. These results suggest potential regulatory roles for DNA methylation in bovine mammary gland processes during S. aureus mastitis and serves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 87 publications
(95 reference statements)
5
23
0
Order By: Relevance
“…The genome-wide DNA methylation patterns of mammary glands producing milk with various fat/protein contents were compared to identify DMCs that may influence the synthesis of milk protein or fat. Approximately half of the DMCs out of 706, 2420, and 1645 DMCs identified from the comparisons of HMF vs. LMF, HMP vs. LMP, and HMFP vs. LMFP, respectively, are located in intergenic regions, while only about 20% are located in promoter regions, thereby corroborating previous reports in dairy and goat mammary gland tissues [36,43]. This report also corroborates data on single nucleotide polymorphism (SNP) mapping in cattle and humans [44][45][46].…”
Section: Discussionsupporting
confidence: 88%
“…The genome-wide DNA methylation patterns of mammary glands producing milk with various fat/protein contents were compared to identify DMCs that may influence the synthesis of milk protein or fat. Approximately half of the DMCs out of 706, 2420, and 1645 DMCs identified from the comparisons of HMF vs. LMF, HMP vs. LMP, and HMFP vs. LMFP, respectively, are located in intergenic regions, while only about 20% are located in promoter regions, thereby corroborating previous reports in dairy and goat mammary gland tissues [36,43]. This report also corroborates data on single nucleotide polymorphism (SNP) mapping in cattle and humans [44][45][46].…”
Section: Discussionsupporting
confidence: 88%
“…Methylation alteration was also predicted as one potential epigenetic regulatory mechanism underlying sperm fertility differences caused by age and other stressors such as heat or oxidative stress ( Lambert et al, 2018 ; Rahman et al, 2018 ; Wyck et al, 2018 ; Takeda et al, 2019 ). Moreover, epigenomic profiling of somatic tissues such as the liver, brain, and mammary gland tissues revealed that epigenetic modifications impact bovine development, health, and productivity ( Zhou Y. et al, 2016 ; Kweh et al, 2019 ; Wang et al, 2020c ). For example, DNA methylation is involved in the regulation of SIRT6 promoter activity during bovine adipocyte differentiation ( Hong et al, 2018 ).…”
Section: Evidence Of the Impacts Of Epigenetic Processes On Livestockmentioning
confidence: 99%
“…Furthermore, a plethora of DMRs were identified in bovine mammary gland tissues in response to mastitis caused by different pathogens, including Escherichia coil and S. aureus , revealing crucial regulatory roles of DNA methylation in mammary immunity during mastitis ( Sajjanar et al, 2019 ; Wu et al, 2020b ). Moreover, genome-wide DNA methylation alteration in the format of C m CGG was significantly related to the immune response to S. aureus -induced mastitis, and several genes including IL-6R , TNF , BTK , IL-1R2 , and TNFSF8 were identified as potential epigenetic markers of S. aureus mastitis ( Wang et al, 2020c ). DMRs were also identified in peripheral blood from mastitis-infected cattle, further demonstrating the importance of DNA methylation in host immune response ( Song et al, 2016 ; Ju et al, 2020 ).…”
Section: Evidence Of the Impacts Of Epigenetic Processes On Livestockmentioning
confidence: 99%
“…There are a wide range of phenotypes that producers must consider to maximize the health and production of their livestock, and DNA methylation has been shown to influence many of those phenotypes. DNA methylation has been associated with mastitis in dairy cattle ( Ju et al, 2020 ; Wang et al, 2020 ), the rate of egg laying in chickens ( Omer et al, 2020 ), beef tenderness in cattle ( Zhao et al, 2020 ), wool fiber production in goats ( Xiao et al, 2020 ), fat deposition in swine ( Zhang et al, 2016 ), and milk production in dairy cattle ( Liu et al, 2017 ) ( Figure 3 ). The diversity of traits associated with DNA methylation patterns in a variety of species highlights the significance of methylation in determining phenotype.…”
Section: Epigenetics and Phenotype Connectionmentioning
confidence: 99%
“…The other intermediates in the demethylation pathway, 5-formylcytosine and 5-carboxylcytosine, are not stable and therefore are not considered viable epigenetic markers. The methylation and demethylation pathways yield two stable epigenetic marks, 5-mC and 5-hmC, which have been used to investigate the association of epigenetic modifications with economically important traits ( Skvortsova et al, 2017 ; Wang et al, 2020 ).…”
Section: Introduction To Epigenetics In Livestockmentioning
confidence: 99%